2019
DOI: 10.1002/cbic.201900358
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Route toward 6‐Methylated Baeocystin and Psilocybin

Abstract: Psilocybin and its direct precursor baeocystin are indole alkaloids of psychotropic Psilocybe mushrooms. The pharmaceutical interesti np silocybin as at reatment optiona gainst depression and anxiety is currently being investigated in advanced clinicalt rials. Here, we reportabiocatalytic route to synthesize 6-methylated psilocybin and baeocystin from 4-hydroxy-6methyl-l-tryptophan, which was decarboxylated and phosphorylated by the Psilocybec ubensis biosynthesis enzymes PsiD and PsiK. N-Methylation was catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…The iterative methylation of norbaeocystin to psilocybin (Figure A) by PsiM is thought to be a rate‐limiting critical step since N ‐methyltransferases are comparably slow enzymes with k cat values ranging between 0.12 h −1 to 0.58 s −1 . Previous studies demonstrated increased psilocybin yields, when Escherichia coli SAH nucleosidase and adenine deaminase were added to the PsiM reaction to irreversibly remove SAH from the chemical equilibrium . Hence, we hypothesized SAH could inhibit PsiM and ran assays in the presence of SAH, ranging between 1–16 m m .…”
Section: Resultsmentioning
confidence: 98%
“…The iterative methylation of norbaeocystin to psilocybin (Figure A) by PsiM is thought to be a rate‐limiting critical step since N ‐methyltransferases are comparably slow enzymes with k cat values ranging between 0.12 h −1 to 0.58 s −1 . Previous studies demonstrated increased psilocybin yields, when Escherichia coli SAH nucleosidase and adenine deaminase were added to the PsiM reaction to irreversibly remove SAH from the chemical equilibrium . Hence, we hypothesized SAH could inhibit PsiM and ran assays in the presence of SAH, ranging between 1–16 m m .…”
Section: Resultsmentioning
confidence: 98%
“…Recent work identified the genes encoding psilocybin biosynthesis enzymes in Psilocybe and other genera [9] . The metabolic pathway was shown by the activity of four Psilocybe cubensis enzymes (PsiD, PsiH, PsiK, and PsiM), which provide l ‐tryptophan decarboxylase, indole‐4‐monooxygenase, kinase, and N ‐methyltransferase activity, respectively [9a,10,11] . Characterization of these enzymes confirmed l ‐tryptophan as the first substrate in the pathway.…”
Section: L‐tryptophan‐derived Natural Products In Psilocybe Speciesmentioning
confidence: 98%
“…773,735 CCS reads were generated. Quast (Gurevich et al 2013) was used to assess the quality of the input fasta sequence file (N50 = 13.9Kb) and the output assembly fasta file (3.33Mb N50).…”
Section: Sequencingmentioning
confidence: 99%
“…This compound has been classified as a “breakthrough therapy” for depression by the FDA ( Johnson and Griffiths 2017 ). The psilocybin pathway was identified by Fricke et al, but to date no public references exist in NCBI with N50s longer than 50kb ( Fricke et al 2017 ; Blei et al 2018 ; Fricke et al 2019a ; Fricke et al 2019b ; Blei et al 2020 ; Demmler et al 2020 ; Fricke et al 2020 ). A more contiguous genome assembly can assist in further resolution of the genetic diversity in the fungi’s secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%